Temperature dependent Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets - Pawbake, Amit S.; Erande, Manisha B.; Jadkar, Sandesh R.; Late, Dattatray J. (RSC Advances, 2016)
The present investigation deals with temperature dependant Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets. The temperature dependent study illustrates that softening of the A(g)(1), B-2g and A(g)(2) modes occurs as the temperature increases from 78 K to 573 K. The calculated temperature coefficients for the A(g)(1), B-2g and A(g)(2) modes were found to be -0.028 cm(-1) K-1, -0.028 cm(-1) K-1 and -0.018 cm(-1) K-1 respectively. The observed phenomenon can be utilized for characterizing other emerging two-dimensional inorganic layered materials with atomic thickness.